1990
DOI: 10.1111/j.1365-2044.1990.tb14624.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term patient‐controlled analgesia in children

Abstract: SummaryThree children who received patient-controlled analgesia ,for periods of up to 41 days are described. In each casi> putientcontrolled analgesia allow,ed pain control to be achieved in dificult situations. No patient developed tolerance or clinical signs of dependence. This use qf long-term patient-controlled analgesia warrants ,further evaluation. Key wordsAnalgesia; postoperative, patient-controlled. Surgery; paediatric.Patient-controlled analgesia (PCA) is becoming well accepted in the management of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…A number of studies have demonstrated that patients in pain readily self-administer opioids using a patient-controlled analgesia procedure, and some studies suggest that the amount of drug self-administered varies directly with the level of pain being experienced (e.g., Berman et al, 1990; Gil et al, 1990; Graves et al, 1985; Mowbray & Gaukroger, 1990; Parker et al, 1991; Schechter et al, 1988; Sidebotham et al, 1997). Consistent with the clinical data, Zacny and colleagues (1996) reported that when normal, healthy volunteers were given the opportunity to self-administer fentanyl intravenously, drug self-administration was significantly greater in the presence of experimentally induced pain than in the absence of pain (Zacny et al, 1996).…”
Section: 0 Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that patients in pain readily self-administer opioids using a patient-controlled analgesia procedure, and some studies suggest that the amount of drug self-administered varies directly with the level of pain being experienced (e.g., Berman et al, 1990; Gil et al, 1990; Graves et al, 1985; Mowbray & Gaukroger, 1990; Parker et al, 1991; Schechter et al, 1988; Sidebotham et al, 1997). Consistent with the clinical data, Zacny and colleagues (1996) reported that when normal, healthy volunteers were given the opportunity to self-administer fentanyl intravenously, drug self-administration was significantly greater in the presence of experimentally induced pain than in the absence of pain (Zacny et al, 1996).…”
Section: 0 Introductionmentioning
confidence: 99%
“…15 The pain relief methods used in the intraoperative period for the study patients were mainly parenteral opioids (573 i.e. 87.9%) and regional blocks mainly caudal blocks (46 i.e.…”
Section: Resultsmentioning
confidence: 99%
“…[6] In addition, the trend for improved safety of drug administration using computerized systems reduces medical errors in drug administration. [15] The implication ofestablishing the current trend for intraoperative pain relief in pediatric patients is enormous costs in terms of equipment, drugs and facilities to be used. It is however, cost effective as it improves socioeconomic life.…”
Section: Discussionmentioning
confidence: 99%
“…[15,[18][19][20] Several authors [21,22] noted less opioid use with PCA when compared with staff-controlled analgesia for oropharyngeal mucositis. It is common in children and is best managed by parenteral opioid analgesia, often being required for several weeks.…”
Section: Patient Selection and Indicationsmentioning
confidence: 99%